2021
DOI: 10.2166/wpt.2021.005
|View full text |Cite
|
Sign up to set email alerts
|

Removal of lead from aqueous solutions and wastewaters using water hyacinth (Eichhornia crassipes) roots

Abstract: Dried ground roots of water hyacinth (Eichhornia crassipes) were used for removal of Pb(II) from aqueous solution. Batch adsorption experiments were conducted with the dried roots (0.1 g dry weight) using 100 mg/L of Pb(II) aqueous solution adjusted at pH 5.0. Equilibrium was obtained in 90 min with a 92% removal of Pb(II). The effect of contact time, pH, adsorbent dosage, initial metal ion concentration on the adsorption of Pb(II) were also studied. Kinetic studies indicated that the adsorption of Pb(II) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 54 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…For example, nitrogen and phosphorus are present in high amounts in municipal wastewater, and if recovered, they can be used as bioenergy, fertilizers, and in the production of chemicals [1,5]. High bioaccumulation activities can also be achieved using dried plant material such as roots [63]. Moreover, at the end of the vegetative period of plants when the phytoremediation capacity has ended, the exhausted biomass can be used in the recovery of metals, for example, through incineration or in biogas production, using anaerobic fermentation [64].…”
Section: Discussionmentioning
confidence: 99%
“…For example, nitrogen and phosphorus are present in high amounts in municipal wastewater, and if recovered, they can be used as bioenergy, fertilizers, and in the production of chemicals [1,5]. High bioaccumulation activities can also be achieved using dried plant material such as roots [63]. Moreover, at the end of the vegetative period of plants when the phytoremediation capacity has ended, the exhausted biomass can be used in the recovery of metals, for example, through incineration or in biogas production, using anaerobic fermentation [64].…”
Section: Discussionmentioning
confidence: 99%
“…5 demonstrates that the experimental data were adjusted to the pseudo-secondorder model, both for the systems using the leaf adsorbent and the stem, which obtained linearity coefficients R 2 = 0.99996 (Figure 5b,d). This model assumes that the rate-determining step depends on the physicochemical interactions between the adsorbate and the adsorbent surface groups, thus indicating a chemisorption process [66,67].…”
Section: Pseudo-first-ordermentioning
confidence: 99%
“…Several authors found results adjusted to the pseudo-second-order model using bioadsorbents. For example, Jahangiri et al [67] worked on Pb(II) lead removal from aqueous solutions and wastewater using water hyacinth (Eichhornia crassipes) roots. The kinetic data indicated that Pb(II) adsorption followed the pseudo-second-order model with a reaction rate constant (K) of 0.0127 (mg.g −1 .min −1 ).…”
Section: Pseudo-first-ordermentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional wastewater treatment processes are not sufficiently eliminated heavy metals including Cr [ 18 ]. But, advanced water treatment technologies such as membrane separation processes, advanced oxidation processes, ozonation, adsorption, and membrane bioreactors achieved high Cr removal [ 6 , 19 21 ]. Recently, advanced wastewater treatment technologies are considered the state of the art in heavy metal removal [ 22 ].…”
Section: Introductionmentioning
confidence: 99%